PENGARUH SUPERVISI DAN SERTIFIKASI TERHADAP KINERJA GURU (STUDI KASUS PADA SEKOLAH MENENGAH PERTAMA NEGERI 7 PALU) - Najemiah, Andi (Katalogis, 2017)
The research is aimed to analize the influence of supervision and certification on teacherâ€™ performance in SMPN 7 Palu with explanative approach. There are 3 (three) variables studied: 1) supervision, 2) certification, and 3) performance of teachers with multiple regression analysis. The population includes all certified-civil servants teachers in SMPN 7Â as many as 33 people. Based on the test results, R square is 0.185 or 18.50% that means that independent variables (supervision X1 and certification X2) influence the teacher performance of 18.50% is influenced by other variables that are not included in this study. The estimation of R is 0.430 or 4,30%, which means that supervision and certification correlates strongly with teachersâ€™ performance in SMPN 7 Palu.